Geology of the Golobar and Rumaceo faults, Basque-Cantabrian Pyrenees - Eloi Carola; Josep Anton Muñoz (Journal of Maps)
The lateral transition between different styles of deformation is crucial for understanding local-scale structures since it influences orogenic reconstructions at the crustal scale. This is especially important at the westernmost Basque-Cantabrian Pyrenees, where the transition from the thin-skinned Basque-Cantabrian Pyrenees to the thick-skinned Cantabrian Mountains remains a subject of debate. To address this, detailed geological mapping and proper fault characterisation are critical. This research focused on the surface characterisation of the Golobar Fault System, one of the faults located at the transition between the two styles of deformation. The results of this study include not only a detailed geological map of the Golobar Fault System but also its integration with neighbouring seismic sections and well data. This approach enhances the understanding of the deeper portions and lateral thickness variations, thereby providing a more comprehensive understanding of the Golobar area within the regional framework.